1984
DOI: 10.1111/j.1463-6395.1984.tb00810.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Polarization and Innervation of the Pars Inferior Sensory Epithelia of the Herring Labyrinth

Abstract: Jensen, J . C. 1984. On the polarization and innervation of the pars inferior sensory epithelia of the herring labyrinth. (Zoological Laboratory, University of Aarhus, Denmark.) -Acta 2001. (Stockh.) 65, 61-74.The macula sacculi and the macula lagenae of the herring, Clupea harengus L., were examined by light microscopy. the macula lagenae is large compared ti1 what is normal among non-ostariophysan fishes. the morphological polarization of the hair cells in the inferior maculae shows a pattern which is simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

1987
1987
1994
1994

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
1
9
1
Order By: Relevance
“…His excellent drawing shows that the wide fibres are restricted to one region of the epithelium where they form branched terminations, while the remaining part of the sensory organ is innervated exclusively by thin nerve fibres. Similar observations have been made in the macula sacculi and the macula lagenae in both non-otophysine and otophysine teleosts (Wegner 1982;Saidel & Popper 1983a, 6;Jensen 1984;Mathiesen 1985;Saidel 1988) as well as in the macula utriculi (Mathiesen 1985;Saidel et al 1990a) plus in the anterior and in the horizontal cristae ampullares in nonotophysine fishes (Mathiesen 1985).…”
Section: The Innervation Of the Inner Ear Sensory Organssupporting
confidence: 75%
See 2 more Smart Citations
“…His excellent drawing shows that the wide fibres are restricted to one region of the epithelium where they form branched terminations, while the remaining part of the sensory organ is innervated exclusively by thin nerve fibres. Similar observations have been made in the macula sacculi and the macula lagenae in both non-otophysine and otophysine teleosts (Wegner 1982;Saidel & Popper 1983a, 6;Jensen 1984;Mathiesen 1985;Saidel 1988) as well as in the macula utriculi (Mathiesen 1985;Saidel et al 1990a) plus in the anterior and in the horizontal cristae ampullares in nonotophysine fishes (Mathiesen 1985).…”
Section: The Innervation Of the Inner Ear Sensory Organssupporting
confidence: 75%
“…The density of the sensory cells Regional differences in the spatial distribution of the receptor cells within the same sensory organ are found in Synodontis as well as in other teleosts (Dale 1976;Platt 1977;Popper & Hoxter 1984Mathiesen 1985;Yan et al 1991); in addition, a rather great interspecific variation in hair cell density is known among the piscine vertebrates (Dale 1976;Corwin 1977;Platt 1977;Popper 1978;Popper & Northcutt 1983;Jensen 1984;Popper & Hoxter 1984;Mathiesen 1985;Mathiesen & Popper 1987).…”
Section: The Orientation Of the Sensory Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although physiological and neuroanatomical data are not extensive, it has been demonstrated that horizontally and vertically oriented cells on the saccular macula in species other than members of the order Otophysi are innervated hy separate portions of the saccular branch of the eighth nerve Popper 1983a, 1983b;Jensen 1984;Mathiesen 1985). Although physiological and neuroanatomical data are not extensive, it has been demonstrated that horizontally and vertically oriented cells on the saccular macula in species other than members of the order Otophysi are innervated hy separate portions of the saccular branch of the eighth nerve Popper 1983a, 1983b;Jensen 1984;Mathiesen 1985).…”
Section: The Role Of the Central Nervous Systemmentioning
confidence: 99%
“…Since innervation studies indicate that individual eighth nerve neurons innervate small areas of the saccular macula Popper 1983a, 1983b;Jensen 1984;Mathiesen 1985), each frequency would maximally stimulate different groups of neurons. One would involve differences in otolith motion (different "motionals") for different frequencies .…”
Section: Regionalizationmentioning
confidence: 99%